2021
DOI: 10.1021/acsphotonics.0c01058
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Parametrized Metasurface Design Using Adjoint Optimization

Abstract: Optical metasurfaces are planar arrangements of subwavelength meta-atoms that implement a wide range of transformations on incident light. The design of efficient metasurfaces requires that the responses of and interactions among meta-atoms are accurately modeled. Conventionally, each meta-atom’s response is approximated by that of a meta-atom located in a periodic array. Although this approximation is accurate for metastructures with slowly varying meta-atoms, it does not accurately model the complex interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 51 publications
0
61
0
Order By: Relevance
“…More TO-designed meta-lens can be checked in the references [17,81,82]. In addition, the general adjoint-based optimizations [83,84] have been reported by Mansouree et al [74] for designing a double-wavelength nano-post meta-lens as shown in Fig. 6 (d).…”
Section: Meta-lensmentioning
confidence: 89%
See 1 more Smart Citation
“…More TO-designed meta-lens can be checked in the references [17,81,82]. In addition, the general adjoint-based optimizations [83,84] have been reported by Mansouree et al [74] for designing a double-wavelength nano-post meta-lens as shown in Fig. 6 (d).…”
Section: Meta-lensmentioning
confidence: 89%
“…Here the inter-post and inter-layer coupling were comprehensively taken into consideration. The systemically designed dual-λ metalens showed the near-diffraction-limited focusing ability and the intensity distributions Moreover, there is increasing attention on the DL-assisted meta-lens design [84]. A specific example can be found from the Pestourie's report [85], where they presented an active-learning algorithm to reduce at least one order of magnitude of the training time for the surrogate model.…”
Section: Meta-lensmentioning
confidence: 99%
“…Other computational frameworks relying on gradient based architecture have been proposed in Refs. [87][88][89] but they often do not reach the global designs.…”
Section: D Large-scale Rgb Metalensmentioning
confidence: 99%
“…It is worth mentioning that due to the simulation cost, optimization of full-metalenses have mostly been considered for 2D metalenses (cylindrical lens) , 84,85,[89][90][91][92][93] considering different optimization architectures and various numerical apertures. In the present work, we focus only on 3D spherical designs where the focusing is maintained along the three spatial dimensions at the visible regime.…”
Section: D Large-scale Rgb Metalensmentioning
confidence: 99%
“…This FOM variation is then associated with the fitness of the design parameters. In the topology optimization method based on homogenisation [17,18] or shape optimization [19], the gradient of the FOM, is used to update simultaneously the design parameters vector. This strategy consisting of simultaneously pushing the design vector elements at each iteration, enforces the local nature of this kind of optimizer.…”
Section: Introductionmentioning
confidence: 99%